Análisis del comportamiento de sistemas de contención en excavaciones para subsuelos en edificios de la ciudad de Salta - Barcena, Exequiel Agustín (2020)
Population growth in large cities such as Salta generate an increase in the demand for housing, the concentration of which tends to be in the downtown area, since this is where the institutions dedicated to commerce, administration, housing and even recreation are generally located. To satisfy this population demand, high-rise buildings with one, two and even three-bedroom apartments are used, plus a kitchen-laundry room, bathroom and living room for homes and administrative offices, most with their own parking. Like any city, this activity is regulated by the Building Code and the Urban Planning Code, which, depending on the area, limits the dimensions of the buildings, as well as their uses and other characteristics. Dueto height limitations, the trend is to choose subfloors whose space is intended for the protection of ve hieles, thus taking full advantage of the available dimensions. However, opting for this solution generates new problems, since, at a deeper excavation, the chances of collapse and structural damage to neighboring buildings increase, therefore, the challenges that the engineers in charge will have to tace will be greater. This project pursues the search for solutions to the proposed problem through the implementation of new excavation and containment systems. For the search for these solutions, different software was used that allowed the study and verification of them.